The role of information and behavioral biases in consumer choice for climate friendly proteins - Alieva, Madina (2021)
The transition from animal towards alternative proteins can help reduce the negative impact of the food systems on the environment and human health. To promote healthier and more sustainable food systems, consumers around the world are encouraged to explore alternative diets and switch towards more environment-friendly protein sources. However, development of environmentally friendlier and healthier protein sources that consumers will accept introduces a challenge as factors influencing consumer acceptance of alternative proteins remain unclear. In two studies, the present work evaluates the role of information and behavioral biases in food choices of young consumers for climate friendly proteins. Data were collected by the means of implementing the tools of experimental economics. The revealed findings of the first study indicate that it is hard to convince younger consumers (pupils) to try a novel climate friendly protein product regardless of whether or not they were provided with information about health or environmental benefits. Nevertheless, when asked to state the price beliefs of the novel product, the children mostly indicated higher price for the climate friendly product as compared to its conventional alternative, which in turn indicates higher value assigned to the product. The second study analyzed the effect of behavioral biases on consumer food choice and how it reflects on the WTA-WTP disparity. The results are in line with academic literature implying that the disparity is present and subject to the substitution effect. Moreover, it was found that consumers value locally produced products more than conventionally produced products by stating average WTP premiums of up to 6.5 and 8.5 SEK for locally manufactured tofu and rapeseed oil.